(untitled) (Research, Society and Development, 2020)
Objective: To identify the profile of herbal medicines most commercialized in a magistral pharmacy in the municipality of Sousa, Paraíba/PB, Brazil. Methodology: This is a documentary, retrospective and descriptive study on the most widely used herbal medicines in the handling pharmacy over a period ofJune 2018 to August 2019. Data collection was carried out based on pharmacy databases analyzed, with the following points assessed: which plants are part of the herbal formulations dispensed and which pharmaceutical form. Tables were used to evaluate this information. Results: A total of 29 herbal medicines manipulated and distributed in the largest number of master pharmacie mentioned. According to the verified bases, 6 different dosage forms were used, namely: capsules, sachets, shot, syrup, soap and cream. Final considerations: It was observed that the most frequent formulation in herbal preparations was the capsule. In addition, it was possible to conclude that there was a predominance in the acquisition of herbal medicines with aniolytic action, followed by those that aid in weight loss.